Pengaruh Pemahaman Perpajakan, Tarif Pajak, Dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak (Studi Pada Pelaku Umkm Kecamatan Ngaliyan Semarang) - Shevia Kumala Sari; Rr. Tjahjaning Poerwati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Taxes are meant for equitable growth and development of a country's economy. This research is to find empirically regarding the effect of understanding taxation, tax rates, and tax sanctions on MSME taxpayer compliance. The research data is quantitative data generated from primary data. This study uses MSME taxpayers in Ngaliyan District, Semarang as respondents. The sample of this study consisted of 656 MSMEs in the Cooperatives and MSMEs Office of Semarang City. This study uses the Non Random Sampling method for sampling. The sample of this research is 100 respondents. The results of this study are that understanding of taxation influences MSME taxpayer compliance, while tax rates and tax sanctions do not affect MSME taxpayer compliance. Keyword: Understanding of Taxation, Tax Rates, Tax Sanctions